New insights in technology characterization of medieval Valencia glazes. (12th March 2015) - Romero‐Pastor, J.; García‐Porras, A.; Van Grieken, R.; Potgieter‐Vermaak, S.; Coll‐Conesa, J.; Cardell, C.
<x xml:space="preserve">Abstract</x> This study shows the first Raman microscopy (RM) and scanning electron microscopy with energy dispersive X‐ray spectroscopy (SEM‐EDX) characterization of two 14th and 15th century lead‐glazed and luster ceramics from the Manises and Paterna workshops (Valencia, Spain) produced after the Aragon Christian conquest of the Iberian Peninsula (14th century). According to experts, these coetaneous ceramics were most probably involved in a process of technological transfer from the Islamic area of Southeast Spain to the Christian area of Valencia (East Spain) at the beginning of the 14th century; later on, the celebrated Manises and Paterna workshops were formed. Although these ceramics have been studied widely in terms of production technology (ceramic body, glazes and luster) using an array of diverse analytical techniques, until now, an RM study has not been carried out. This paper presents results regarding the complex chemical composition of the glaze and luster coloring agents, and the quality of color manufacturing processes, elucidating firing conditions via spectral components analysis (i.e., Qn for stretching/bending components) and polymerization index (Ip), emphasizing chronology and pigment technology changes between both Valencian workshops. Coloring agents identified in glazes and lusters were cobalt present in blue glazes, copper in greenish glazes, copper and cobalt in the turquoise glaze, and pyrolusite in black glazes. Tin oxyde was used as an opacifier in white glazes. Two luster manufacture recipes were recognized mainly based on copper and silver compounds. Calculated firing temperatures were up to 1000 °C for white glazes and up to 600 °C for luster and color glazes. Copyright © 2015 John Wiley & Sons, Ltd.